2020
DOI: 10.5603/cj.a2020.0065
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 — Toward a comprehensive understanding of the disease

Abstract: The evidence on the pathophysiology of the novel coronavirus SARS-CoV-2 infection is rapidly growing. Elucidating why some patients suffering from COVID-19 are getting so sick, while others are not, has become an informal imperative for researchers and clinicians around the globe. The answer to this question would allow rationalizing the fear surrounding this pandemic. Understanding of the pathophysiology of COVID-19 relies on unraveling of interplaying mechanisms, including SARS-CoV-2 virulence, human immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 128 publications
0
68
0
3
Order By: Relevance
“…23,31,32 (3) The current uncertainties related to SARS-CoV-2 pathogenesis. [33][34][35] (4) The fears and concerns in the laboratory and biobank staff and in the general population regarding manipulation of samples from COVID-19positive or suspected patients. 36-39 (5) The fact that contagion may occur after handling plastic bags and other material coming from the clinical pulmonary department, since it was shown that SARS-CoV-2 can remain on many different surfaces for several hours or days.…”
Section: Biological Risks Associated With Preparation Of Blood Derivamentioning
confidence: 99%
“…23,31,32 (3) The current uncertainties related to SARS-CoV-2 pathogenesis. [33][34][35] (4) The fears and concerns in the laboratory and biobank staff and in the general population regarding manipulation of samples from COVID-19positive or suspected patients. 36-39 (5) The fact that contagion may occur after handling plastic bags and other material coming from the clinical pulmonary department, since it was shown that SARS-CoV-2 can remain on many different surfaces for several hours or days.…”
Section: Biological Risks Associated With Preparation Of Blood Derivamentioning
confidence: 99%
“…The microdroplets with the virus particles will reach another person and can enter them via epithelial conjunctiva and the upper respiratory tract cells [41]. However, the aerosol transmission of viral particles is still under investigation and it has been estimated that these particles can reside in an unventilated space for several hours [42]. Recently, several researchers suggested that the aerosol can stay longer in the air with the viral load, which may transmit the virus eff ectively in a closed or air conditioned environment [43,44].…”
Section: Pathophysiology Of Sars-cov-2mentioning
confidence: 99%
“…This viral infection can lead to acute coronary syndromes, arrhythmias, and heart failure and even death [33]. Cardiovascular conditions seem to be a threat in patients with SARS-CoV-2 [34]. SARS-CoV-2 is associated with cardiac dysfunction [35].…”
Section: Sars-cov-2 To Cardiovascular Disease Conditions In Diabetic mentioning
confidence: 99%